If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(2j-7)=12j
We move all terms to the left:
6(2j-7)-(12j)=0
We add all the numbers together, and all the variables
-12j+6(2j-7)=0
We multiply parentheses
-12j+12j-42=0
We add all the numbers together, and all the variables
-42!=0
There is no solution for this equation
| –0.4x+4=–1.6 | | 20+53.45x=58.45x | | 21=-3k | | x*61=4 | | 3y+-9=0 | | 20x+10x=420 | | -6(2r-11)=-12r | | x2-8x+16=36 | | 12(5x4.5)=36 | | 6/w=10/2 | | 19=y+11 | | 6n+15=-17n+19n-1 | | 5(2-2x)+5x=15 | | 20x+30x=420 | | 3x+4+3=-3 | | 3x+(-9)=(-3) | | 4/9g+8=1/6g+1 | | 6n=60-2n | | 2x-5/x+6=-5/7 | | 2u−–4=8 | | -19j+18=-6(7j+20) | | 180=5y+38+17y-4 | | 6(x+1)+5=15-2+4x | | x=19+3/5 | | 112(x−76)=1+x | | -19j+18=-6(7j+20 | | X=1.6y+48 | | 8(x-5)=18x | | -5p-p=-4(p-6)-2(-6+4p) | | 5(w+7)=-40 | | 3x+10°-10°=180° | | 180=7x+30+11x-24 |